To Help or Not to Help: Intervening in Cyberbullying Among Chinese Cyber-Bystanders - Leung, Angel Nga Man (Frontiers in Psychology, 2021)
Cyberbullying has become a serious concern among Internet users worldwide. However, relatively little is known about individuals who witness cyberbullying and how they behave. A bystander is someone who sees bullying or other forms of aggressive or violent behavior that targets someone else and who may choose to respond by either being part of the problem (a hurtful bystander), or part of the solution (a helpful bystander). Few studies examined the phenomena of cyber-bystanders in Chinese populations. Guided by the five-step bystander theoretical model developed by Darley and Latané, (1970) and the Theory of Planned Behavior (TPB; Ajzen, 1991), this study, addressed this gap to understand how the characteristics of cyber-bystanders explained their intervention in cyberbullying in a Chinese population. This study tested two pre-registered hypotheses: 1) controlling for age and gender, awareness of cyberbullying, attitudes, subjective norm and perceived behavioral control to intervene; plus past experience with cyberbullying (measured as past experience in cyberbullying perpetration and victimization), felt responsibility, and self-efficacy to intervene with regard to cyberbullying would explain cyber-bystanders’ intention to intervene in cyberbullying, and 2) cyber-bystanders’ intention to intervene cyberbullying would positively explain their intervening behavior. A total of 581college students with experience of witnessing cyberbullying were included in the analysis. Applying structural equation modelling with observed variables, a path analysis model was built to test the hypotheses, this study also conducted exploratory analyses by including direct paths from characteristics of cyber-bystanders to explain intervening behavior Results found that only awareness of cyberbullying, subjective norm) and self-efficacy to intervene positively explained intention to intervene cyberbullying, therefore, hypothesis 1 was partly supported. Also, intention to intervene cyberbullying positively explained intervening behavior, therefore, hypothesis 2 was supported. For the exploratory analysis, intention to intervene partially mediated the relation between subjective norm to intervene and intervening behavior; and intention to intervene also partially mediated the relation between self-efficacy to intervene and intervening behavior. In addition, past experience in cyberbullying victimization also positively and directly predicted intervening behavior. Findings provided a foundation for designing future intervention programmes to mobilize cyber-bystanders to become “upstanders”.